2019
DOI: 10.1021/jacs.8b11473
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Kinetics versus Thermodynamics in Surface-Assisted Ullmann Coupling on Gold and Silver Surfaces

Abstract: Surface-assisted Ullmann coupling is the workhorse of on-surface synthesis. Despite its obvious relevance, many fundamental and mechanistic aspects remain elusive. To shed light on individual reaction steps and their progression with temperature, temperature-programmed X-ray photoelectron spectroscopy (TP-XPS) experiments are performed for a prototypical model system. The activation of the coupling by initial dehalogenation is tracked by monitoring Br 3d core levels, whereas the C 1s signature is used to follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(154 citation statements)
references
References 54 publications
11
141
0
2
Order By: Relevance
“…In addition, the linear chain is uniformly organized with the peanut shape, while no metal atom can be recognized inside the chain, indicating that OM intermediates might have already been transformed into the covalently coupled nanostructures. Nevertheless, these chains are still terminated with Br atoms with the typical bright protrusion ends as generally reported in literature 43 . Notably, dissociated Br atoms from parent molecules also desorb from surface during thermal annealing, as discovered in Fig.…”
Section: Resultssupporting
confidence: 63%
“…In addition, the linear chain is uniformly organized with the peanut shape, while no metal atom can be recognized inside the chain, indicating that OM intermediates might have already been transformed into the covalently coupled nanostructures. Nevertheless, these chains are still terminated with Br atoms with the typical bright protrusion ends as generally reported in literature 43 . Notably, dissociated Br atoms from parent molecules also desorb from surface during thermal annealing, as discovered in Fig.…”
Section: Resultssupporting
confidence: 63%
“…We report the formation of ordered and extended 2D supramolecular network of 1-(4"-cyanobiphenyl)-4-(4"-methoxybiphenyl)-2,5-bis(propyloxy)benzene (LDipCC) molecule on a Si(111)-B surface. Scanning Tunnelling Microscopy (STM), Density Functional Theory (DFT) calculations, which is a powerful tool to elucidate molecular adsorption on surfaces, 25,26,27 and STM simulations were used to demonstrate that the LDipCC molecule is self-assembled into a highly homogeneous parallel arrangement on the Si(111)-B surface. In addition, Si(111)-B is a weakly reactive surface, anti-parallel arrangement has been mostly observed on Cu(111), but not on less reactive surfaces such as Au(111) and HOPG.…”
Section: Large-extended 2d Supramolecular Network Of Dipoles With Parmentioning
confidence: 99%
“…The assessment of reaction pathways and products is usually performed employing scanning tunneling microscopy (STM) in combination with x ‐ray photoelectron spectroscopy (XPS), but neither of these techniques provide detailed time and temperature resolution of a dynamically evolving process. In this respect, temperature‐programmed XPS (TP‐XPS) is a unique tool to discern fundamental mechanistic aspects of thermally activated surface reactions that has also been applied to study dehalogenative aryl–aryl coupling reactions . Such investigations have shown that the chemical transformations reflected in the halogen XPS signal are identical for many substrates, starting with the halogen's dissociation from the molecular precursor, accompanied by its chemisorption to the substrate, and its eventual desorption from the surface.…”
Section: Figurementioning
confidence: 99%